The Implementation of The Kaleng Impian Program in Character Education for Students - Mazro’atul Ulum; Slamet Slamet (Urwatul Wutsqo)
Character education is an effort to instill virtuous values aimed at shaping a generation with strong morals in accordance with societal norms. This study aims to examine the impact of the Kaleng Impian (Dream Can) program in instilling character education, as well as to identify the supporting and inhibiting factors in its implementation among students at MI NU Hidayatun Najah Tuban. This research is a qualitative descriptive study using a case study approach. The research subjects consisted of teachers and students at MI NU Hidayatun Najah Tuban, with data collected through observation, in-depth interviews, and documentation. The study refers to Thomas Lickona’s three components of character education: Moral Knowing, one’s ability to evaluate oneself; Moral Feeling, the drive to do good and the ability to control oneself; and Moral Action, the implementation of moral knowledge and feelings through actions aligned with established norms. Thus, the researcher seeks to explore how the Kaleng Impian program is implemented from the perspective of character education through the lenses of moral knowing, moral feeling, and moral action. The findings reveal that the Kaleng Impian program at MI NU Hidayatun Najah successfully cultivates character values such as responsibility, tolerance, and religiosity based on moral knowing, feeling, and action, thereby contributing to the formation of students' character. However, several inhibiting factors were identified, including limited teacher understanding, low parental involvement, diverse levels of student comprehension, and the absence of a standardized evaluation system